Microstructural design and mechanical performance of epoxy/carbon nanotube fiber composite. (September 2022) - Seraji, Amir Abbas; Aghvami-Panah, Mohammad; Zadhoush, Ali; Salimian, Saeed; Khoshnevis, Hamed
In this paper, carbon nanotube (CNT) fiber is chemically modified through a post-spinning process with an acid treatment and epoxy infiltration. Thermo-gravimetric analysis (TGA), FTIR, and Raman spectroscopy revealed that acid treatment reduced impurities of CNT fibers and induced the formation of carboxylic functional groups on the CNTs surface that positively affect the strength; however, some defects on the surface of the nanotubes were induced that negatively affect the elastic modulus. After the epoxy infiltration procedure, it was revealed that the pores of CNT fiber were filled with epoxy resulting in improved interfacial interaction between CNT bundles either through an interlocking of polymer chains wrapping around the tubes or even by creating covalent bonds between the carboxyl-functionalized nanotubes. Comparing the mechanical performance of epoxy/CNT fibers with and without acid treatment indicated that pre-treatment of the fibers with acid before epoxy infiltration caused a reduction in the final modulus. The modulus of epoxy/CNT fiber reaches 103 N/tex and is about 20% higher than the acid-treated counterpart. Acid treatment prior to epoxy resin infiltration generates functional groups on the CNTs surface that enhance the fiber's strength through strong reactions between epoxy chains and CNTs. On the other hand, the structural defects on CNTs imposed by acid lead to a reduction in the elastic modulus.